# On calculating the minor determinant of adjoint matrix

Question:

$A$ is an $n$ order square matrix, and $B=A^{(*)}$ is the adjoint matrix of $A$ (i.e. $AB=BA=\det A\cdot I_n$).

Show that

$$\det B \begin{pmatrix} 1 & 2 & \cdots & k \\ 1 & 2 & \cdots & k \end{pmatrix} = (\det A)^{k-1}\cdot \det A \begin{pmatrix} k+1 & k+2 & \cdots & n \\ k+1 & k+2 & \cdots & n \end{pmatrix}.$$

Here, $B \begin{pmatrix} 1 & 2 & \cdots & k \\ 1 & 2 & \cdots & k \end{pmatrix}$ denotes the $k\times k$ submatrix of $B$ on the top left corner,

$A \begin{pmatrix} k+1 & k+2 & \cdots & n \\ k+1 & k+2 & \cdots & n \end{pmatrix}$ denotes the the $(n-k)\times (n-k)$ submatrix of $A$ on the bottom right corner.

I have tried to use the Laplace expansion theorem but failed.

-

It is actually more related to this. Maybe it is better to express it by partitioning. Given an "invertible" square matrix $A$, $$A = \left(\begin{array}{c|c}A_1 &A_2\\\hline A_3 &A_4\end{array}\right), A^{-1} = \left(\begin{array}{c|c}\hat A_1 &\hat A_2\\\hline \hat A_3 &\hat A_4\end{array}\right)$$ and by stealing the latex code from wikipedia $$\begin{multline} \det{(A^{-1})}=\det\left[ \begin{matrix} A & B \\ C & D \end{matrix}\right]^{-1} = \underbrace{\det\left[ \begin{matrix} I & 0 \\ -D^{-1}C & I \end{matrix}\right]}_1\det\left[ \begin{matrix} (A-BD^{-1}C)^{-1} & 0 \\ 0 & D^{-1} \end{matrix}\right]\\ \underbrace{\det\left[ \begin{matrix} I & -BD^{-1} \\ 0 & I \end{matrix}\right]}_{1} \end{multline}$$ another detail is that $(A-BD^{-1}C)^{-1} = \hat{A}_1$. Therefore $\det{(A^{-1})}=\det{(\hat{A}_1)}\det{(A_4^{-1})}$also $B$ is defined as $$B = \det{(A)} A^{-1} = \left(\begin{array}{c|c}B_1 &B_2\\\hline B_3 &B_4\end{array}\right)$$ partitioned accordingly. From the Schur Complement formula and from $\det{(\alpha A) = \alpha^n\det{(A)}}$, we know that \begin{align} \det{(A^{-1})} &= \det{(A_4^{-1})}\det{(\hat A_1)}\\ &= \det{(A_4^{-1})}\left[ (\det(A))^{-k}\det{(B_1)}\right] \\ &= (\det(A))^{-k}\frac{1}{\det{(A_4)}}\det{(B_1)}\\ &=\frac{1}{\det{(A)}} \end{align} Then, we have the desired result, $$\det{(A_4)} = (\det{(A)})^{k-1}\det{(B_1)}$$
Sorry, I didn't understand how do you get $\det (B)=\det{(A_4^{-1})}\det{(B_1)}$, could you extend it? – NGY Aug 26 '11 at 14:23